Design of digital controller for an armature controlled motor using the digital approximation of a continuous controller / Noraini Ahmad - Ahmad, Noraini (1999)
A digital controller based on the digital approximation of a continuous controller is designed for an armature-controlled motor. Continuous lead, lag and lead-lag controllers are designed to meet the given specifications. The output responses for each of the compensated systems are then obtained using MATLAB. Several digital approximations of the analogue controller that gives the best response are tried out. The purpose of analysis the system is to find the performance specification such as relative stability, speed of response and the accuracy of the given system. The time response of the digital compensated system using the approximation methods are simulated to compare with the time response of the analogue compensated system, in order to choose the best digital approximation method for the given system.